Morphological integrity of the bronchial epithelium in mild asthma. Issue 1 (January 1990) - Lozewicz, S; Wells, C; Gomez, E; Ferguson, H; Richman, P; Devalia, J; Davies, R J
Abstract : In severe asthma bronchial epithelial cells are damaged and detached, and it has been proposed that such damage might lead to the bronchial hyperresponsiveness that characterises asthma. To investigate the relation between airway hyperresponsiveness and epithelial damage, biopsy specimens of the bronchial mucus membrane were obtained at fibreoptic bronchoscopy from 11 patients with mild atopic asthma and airway hyperresponsiveness (provocative concentration of methacholine causing a 20% fall in FEV1 (PC20) less than 1.0 mg/ml), and from 17 healthy non-atopic subjects who did not have airway hyperresponsiveness (PC20 methacholine greater than 8.0 mg/ml). Observers who were blind to the presence or absence of asthma examined the biopsy specimens by light and electron microscopy. Epithelial cells, intercellular spaces, and goblet cells were counted. Intercellular junctional complexes were examined, and a semiquantitative assessment was made of ciliary loss, non-parallel central ciliary filaments, and vacuoles in ciliated cells. There were no differences between the asthmatic and healthy groups in any of these measurements. These findings indicate that airway hyperresponsiveness may be present when there is no apparent change in the structure of the bronchial epithelium.